2010
DOI: 10.1007/s10236-010-0344-9
|View full text |Cite
|
Sign up to set email alerts
|

SLA–chlorophyll-a variability and covariability in the Algero-Provençal Basin (1997–2007) through combined use of EOF and wavelet analysis of satellite data

Abstract: Data reduction and signal decomposition techniques have been applied to a large bio-physical remotely sensed dataset covering the decade 1997-2007. The aim was the estimation of the spatial (basin and sub-basin scales) and temporal (seasonal and interannual) variability of sea level anomalies and chlorophylla concentration in the Algero-Provençal Basin, as well as the study of their covariability. Empirical orthogonal functions, wavelet analysis, singular value decomposition and correlation maps have been succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 42 publications
2
44
0
Order By: Relevance
“…Nevertheless, this part is also characterized by the strongest coupling between chlorophyll a (Chla; a good and prompt proxy for phytoplanktonic biomass) and the displacement of isopycnae. In other words, effects on the phytoplanktonic abundance of nutrient injection in euphotic layer, generated by isopycnae displacements, is much more evident here than in northern and southern areas (Olita et al 2011).…”
Section: Study Areamentioning
confidence: 98%
See 2 more Smart Citations
“…Nevertheless, this part is also characterized by the strongest coupling between chlorophyll a (Chla; a good and prompt proxy for phytoplanktonic biomass) and the displacement of isopycnae. In other words, effects on the phytoplanktonic abundance of nutrient injection in euphotic layer, generated by isopycnae displacements, is much more evident here than in northern and southern areas (Olita et al 2011).…”
Section: Study Areamentioning
confidence: 98%
“…Excluding the shallowest shelf areas, it could be roughly divided in three main parts, considering both circulation and bio-physical characteristics accordingly to our previous study (Olita et al 2011). The southern part, namely the Algerian Basin (AB), is characterized at the surface by the Atlantic Water (AW) flowing into the Mediterranean Sea through the Gibraltar Strait (Millot et al 1999).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…At its start, near 0° longitude, the Algerian Current is fairly narrow (30-50 km), flowing close to the coast. As the current progresses eastward, its width and separation from the coast vary and, due to baroclinic instabilities in its flow, meanders are regularly formed and can eventually detach from the current and become both cyclonic and anticyclonic coastal eddies (Olita et al 2011). Some of the stronger eddies, which are predominantly anticyclonic, may become "open sea eddies" and reach the southern Balearic Islands (Millot 1999).…”
Section: Study Areamentioning
confidence: 99%
“…Hereafter, for the purposes of the present study, we will consider only the Algerian anticyclonic Eddies, indicated with the acronym AEs. The general description of their behaviour, as reported in the bibliography, is that they move along the African coast at a few Km per day and are blocked at the level of the Sardinia Channel (Millot, 1985(Millot, , 1999Font et al, 1998Font et al, , 2004Olita et al, 2011), where they are usually forced by the local topography to detach from the coast and follow a cyclonic pathway (Millot, 1987;Vignudelli, 1997;Cotroneo et al, 2016;Aulicino et al, 2018).…”
mentioning
confidence: 99%